Environmental assessment of certain plans and programmes as contribution to sustainable spatial development - Ulrike Weiland (European Regional Science Association (ERSA), 2002)
Cities and urban regions especially in the West German agglomerations are characterised by an unbroken dynamic development, connected with changes in land use from undeveloped land into settlement areas and traffic zones up to the rural districts far from the cities. Environmental loads, e.g. negative environmental effects on air quality and noise, and adverse affects on valuable habitats are negative consequences of the growing of urban regions. On the other hand, cities and urban regions shall contribute to a sustainable spatial development as agreed to in the Agenda 21 and prescribed by the Regional Planning Law and the Federal Building Code. In order to turn the spatial development of cities and urban regions towards a sustainable spatial development, adequate planning and management instruments are required. The Directive of the European Union on the assessment of the effects of certain plans and programmes on the environment contains a framework, how the member states will have to take into consideration environmental aspects while drawing up or complementing certain plans and programmes. An environmental assessment shall be carried out for plans and programmes, which are likely to have significant environmental effects, e.g. for town and country planning and land use planning, and which set the framework for future development for projects submitted to an environmental impact assessment. The environmental assessment shall take into consideration reasonable alternatives including the zero-alternative. It shall contain a "screening" (necessity-check), a "scoping" (agreement on the scope of investigations), an "environmental report" and consultations of the public. The environmental report shall contain the analyse and evaluation of likely significant positive and negative effects on biodiversity, population and human health, fauna, flora, soil, water, air, climatic factors, material assets, cultural heritage including architectural and archaeological heritage. The Member States shall bring into force the laws, regulations and administrative provisions necessary to comply the Directive up to 2004. The discussion on the implementation of the EU Directive is in full swing. In Germany, each drawing up of a new land use plan or regional plan will require an environmental assessment. In the case of changes or amendments of those plans, it will depend a.o. on the extent and amount of environmental effects of the plan, whether an environmental assessment has to be carried out or not. Whether and how an environmental assessment can be integrated into spatial planning, and whether the landscape plans already carry out environmental assessments or have to be developed further is under discussion controversially. Further questions are e.g. how the subjects of the assessment shall be defined in detail, how results of the environmental assessment can be monitored, how the environmental assessment can be integrated into the planning procedures without taking many financial and personal resources, and how and at which extent the public shall be consulted. The lecture will focus on how the Directive can be realised by spatial and landscape planning, especially which methodical questions spatial and landscape planning will have to solve in order to implement an environmental assessment for plans and programmes according to the EU Directive.
Keywords: 330